Coccoid and spiral Helicobacter pylori differ in their abilities to adhere to gastric epithelial cells and induce interleukin-8 secretion. - Cole, S P (1997)
Helicobacter pylori exists as an actively dividing spiral form and a nonculturable, but viable, metabolizing coccoid form. Both forms are present in the stomach, but their relative pathophysiologic significances are unknown. Here we show that the coccoid form of H. pylori, in contrast to the spiral form, binds poorly to gastric epithelial cells and induces little, if any, interleukin-8 secretion by these cells.